O embodiment nas imagens da tecnocultura do jogar - Ávila, Camila de (Universidade do Vale do Rio dos Sinos, 2024)
The research seeks to observe different manners of embodiment in the images of gaming technoculture and different modes of immersive experience in digital games. Presenting a research problem that pursue to understand how the memory of embodiment is updated in the images of the technoculture of gaming, we seek to generate thinking about a phenomenological perspective of the body. We think of embodiment in these spaces as demanding action: in addition to our body and the machinic, there is a third body in latency, and is only perceived when we play. Each game and device we observe we call “experience territories”: the virtual reality environment, the game world, the space we are exploring, the off-screen environment where our real body is. As empirical objects, the research explores hardware and software: Atari Mindlink (1984), Meta Quest 2 (2020), Dreams of Dalí (2018), Beat Saber (2018), Pixel Ripped 1989 (2018), Art Plunge (2019), Half-Life: Alyx (2020), Pixel Ripped 1995 (2020) and Pixel Ripped 1978 (2023). Endowed with a media-archaeological and archaeogaming perspective, this diversity allows us to look at technoculture from the perspective of audiovisualities: audiovisual power in different devices, becoming that emerges in matter, which for us are games. Our methodology takes place in the following arrangement: Bergsonian intuitive method, guiding the construction of the object and the research problem; development of maps based on excavation movements, dissection, collections of images from our empirics related to the assembly of constellations; experimental and laboratory technical procedures based on the act of playing the games, producing gameplay videos – an act of our action as researcher-player-archaeogamer in these territories using a virtual reality device. We present three constellations that form the embodiment galaxy of gaming technoculture images: point-of-view, contemplative state and mind-body-haptic – where the three coexist. There is a body that exists (or pre-exists) in the sum of everything that forms the game world while it is being played – a latent body, in becoming. The perception of its existence occurs in its manifestation when the game is being played. We have embodiment as this body of the playful subject of technoaesthetic experience, a body that is in between and constituted by the powers of the playful, imagery order and the computational/artifact/materiality order.
Keywords: Embodiment; Tecnocultura; Jogos digitais; Realidade virtual; Technoculture; Digital games; Virtual reality; ACCNPQ::Ciências Sociais Aplicadas::Comunicação